Why choose forceps over ventouse? A qualitative study exploring contextual factors in decision making. (7th June 2011) - Umranikar, A; Fenwick, A; Wiles, R; Cullen, J; Mountfield, J; Cheong, Y
Abstract : Background: Clinical guidelines on instrumental deliveries are mainly skill based. The objective of this study was to identify factors which influence clinicians' decision making in conducting an instrumental delivery. Methods: The study has utilised a qualitative case-study approach comprising observation of the decision-making process during deliveries and follow-up interviews with clinicians. Interview data were transcribed and used alongside observational notes to analyse decision making in each case. Results: Data were collected from 23 cases, the majority of which (n=16) were forceps deliveries. A range of factors related to equipment, training and hospital culture were identified as being discouraging to the use of ventouse. Conclusion: Hospital context and culture have a central role in influencing clinician's decision making. Understanding these factors is a crucial first step in assessing appropriate practice and identifying interventions to change practice.